Humoral responses after second and third SARS-CoV-2 vaccination in patients with immune-mediated inflammatory disorders on immunosuppressants: a cohort study. (May 2022) - Wieske, Luuk; van Dam, Koos P J; Steenhuis, Maurice; Stalman, Eileen W; Kummer, Laura Y L; van Kempen, Zoé L E; Killestein, Joep; Volkers, Adriaan G; Tas, Sander W; Boekel, Laura; Wolbink, Gerrit J; van der Kooi, Anneke J; et al.
Summary: Background: Disease-specific studies have reported impaired humoral responses after SARS-CoV-2 vaccination in patients with immune-mediated inflammatory disorders treated with specific immunosuppressants. Disease-overarching studies, and data on recall responses and third vaccinations are scarce. Our primary objective was to investigate the effects of immunosuppressive monotherapies on the humoral immune response after SARS-CoV-2 vaccination in patients with prevalent immune-mediated inflammatory disorders. Methods: We did a cohort study in participants treated in outpatient clinics in seven university hospitals and one rheumatology treatment centre in the Netherlands as well as participants included in two national cohort studies on COVID-19-related disease severity. We included patients aged older than 18 years, diagnosed with any of the prespecified immune-mediated inflammatory disorders, who were able to understand and complete questionnaires in Dutch. Participants with immune-mediated inflammatory disorders who were not on systemic immunosuppressants and healthy participants were included as controls. Anti-receptor binding domain IgG responses and neutralisation capacity were monitored following standard vaccination regimens and a three-vaccination regimen in subgroups. Hybrid immune responses—ie, vaccination after previous SARS-CoV-2 infection—were studied as a proxy for recall responses. Findings: Between Feb 2 and Aug 1, 2021, we included 3222 participants in our cohort. Sera from 2339 participants, 1869 without and 470 participants with previous SARS-CoV-2 infection were analysed (mean age 49·9 years [SD 13·7]; 1470 [62·8%] females and 869 [37·2%] males). Humoral responses did not differ between disorders. Anti-CD20 therapy, sphingosine 1-phosphate receptor (S1P) modulators, and mycophenolate mofetil combined with corticosteroids were associated with lower relative risks for reaching seroconversion following standard vaccination (0·32 [95% CI 0·19–0·49] for anti-CD20 therapy, 0·35 [0·21–0·55] for S1P modulators, and 0·61 [0·40–0·90] for mycophenolate mofetil combined with corticosteroids). A third vaccination increased seroconversion for mycophenolate mofetil combination treatments (from 52·6% after the second vaccination to 89·5% after the third) but not significantly for anti-CD20 therapies (from 36·8% to 45·6%) and S1P modulators (from 35·5% to 48·4%). Most other immunosuppressant groups showed moderately reduced antibody titres after standard vaccination that did not increase after a third vaccination, although seroconversion rates and neutralisation capacity were unaffected. In participants with previous SARS-CoV-2 infection, SARS-CoV-2 antibodies were boosted after vaccination, regardless of immunosuppressive treatment. Interpretation: Humoral responses following vaccination are impaired by specific immunosuppressants. After standard vaccination regimens, patients with immune-mediated inflammatory disorders taking most immunosuppressants show similar seroconversion to controls, although antibody titres might be moderately reduced. As neutralisation capacity and recall responses are also preserved in these patients, this is not likely to translate to loss of (short-term) protection. In patients on immunosuppressants showing poor humoral responses after standard vaccination regimens, a third vaccination resulted in additional seroconversion in patients taking mycophenolate mofetil combination treatments, whereas the effect of a third vaccination in patients on anti-CD20 therapy and S1P modulators was limited. Funding: ZonMw (The Netherlands Organization for Health Research and Development).